The ketimide ligand is not just an inert spectator: heteroallene insertion reactivity of an actinide-ketimide linkage in a thorium carbene amide ketimide complex - Lu, Erli; Lewis, William; Blake, Alexander J.; Liddle, Stephen T. (Wiley-VCH Verlag, 2014)
The ketimide anion R2C[DOUBLE BOND]N− is an important class of chemically robust ligand that binds strongly to metal ions and is considered ideal for supporting reactive metal fragments due to its inert spectator nature; this contrasts with R2N− amides that exhibit a wide range of reactivities. Here, we report the synthesis and characterization of a rare example of an actinide ketimide complex [Th(BIPMTMS){N(SiMe3)2}(N[DOUBLE BOND]CPh2)] [2, BIPMTMS=C(PPh2NSiMe3)2]. Complex 2 contains Th[DOUBLE BOND]Ccarbene, Th[BOND]Namide and Th[BOND]Nketimide linkages, thereby presenting the opportunity to probe the preferential reactivity of these linkages. Importantly, reactivity studies of 2 with unsaturated substrates shows that insertion reactions occur preferentially at the Th[BOND]Nketimide bond rather than at the Th[DOUBLE BOND]Ccarbene or Th[BOND]Namide bonds. This overturns the established view that metal-ketimide linkages are purely inert spectators.